Histological and histochemical characteristics of the esophagus in local breed donkey (Equus asinus) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Certain advantages of donkeys are still not listed as for other equine species. Moreover, donkeys lack comprehensive scientific studies. The present study examines the histological architecture and histochemical characteristics of the esophagus in the Iraqi local breed donkey (Equus asinus). Materials and Methods: Eight esophagus samples were collected from a local breed donkey. Tissue specimens (~1 cm3 ) were collected from the cervical, thoracic, and abdominal regions of the esophagus and processed via routine histological technique. The tissue sections were stained with hematoxylin and eosin, Massons Trichrome, and combined Alcian blue (pH 2.5) plus PAS (AB-PAS). Results: The esophagus of the local breed donkey had folded mucosa wrapped by thin non-keratinized stratified squamous epithelium. The heights of epithelia of the cervical and thoracic regions of the esophagus were significantly higher than that of the abdominal regions. The lamina propria consisted of dense fibrous tissue that appeared thickest in the thoracic and abdominal regions of the esophagus. The muscularis mucosa disappears at the cervical region, while the thoracic and abdominal regions of the esophagus contain thick, scattered, interrupted bundles of smooth muscle fibers. Tunica submucosa was very thick at the thoracic and abdominal regions of the esophagus, composed of loose connective tissue filled with compound tubular mucoserous esophageal glands. Using a combined AB-PAS stain, mucous alveoli within the esophageal glands indicated strong acidic mucopolysaccharide. Tunica muscularis of the cervical and thoracic regions was built up by striated muscle fibers and turned into smooth type at the abdominal region of the esophagus. Conclusion: The esophagus of the local breed donkey shows considerable histological similarities with the other mammals that make this species reliable as an experimental model of digestive tissue.J. Adv. Vet. Anim. Res., 10(1): 14–20, March 2023http://doi.org/10.5455/javar.2023.j647